Pengaruh Habituasi Nilai Karakter Tanggung Jawab terhadap Pembentukan Profil Pelajar Pancasila Siswa Kelas XI SMAN 1 Benai - Voni Fitria; Hambali Hambali; Supentri Supentri (Departement of Mathematics Education, 2023)
This research is motivated by the phenomenon shown by the weak value of the character of responsibility in the formation of a Pancasila student profile in students at SMAN 1 Benai. Based on a literature study conducted by researchers, habituation is a form of effort to strengthen character, especially the character of responsibility for the formation of Pancasila student profiles. Related to the above, researchers are interested in conducting research with the title the effect of habituation of the character values ​​of responsibility on the formation of Pancasila student profiles of SMAN 1 Benai students. The purpose of this study was to find out whether the habituation of the character values ​​of responsibility has a positive effect on the formation of a Pancasila student profile for class XI students of SMAN 1 Benai. This research method uses descriptive quantitative methods, namely processing data in the form of numbers which are then drawn conclusions. The population in this study amounted to 180 students. Determination of the sample in this study using a sampling quota set at 20%. Thus the sample in this study amounted to 36 students. Based on the results of the study, it was found that the highest indicator was the habituation of getting used to throwing garbage in its place while the lowest indicator was the habituation of a culture of queuing when buying food. However, overall habituation of the character values ​​of responsibility has a positive and significant effect on the formation of students' Pancasila student profiles.